2022
DOI: 10.1177/01445987221112250
|View full text |Cite
|
Sign up to set email alerts
|

A multi-energy load prediction of a building using the multi-layer perceptron neural network method with different optimization algorithms

Abstract: Since cooling and heating loads are recognized as key characteristics for evaluating the energy efficiency of buildings, it appears indisputable that they must be predicted and analyzed for residential structures. Accordingly, the multi-layer perceptron neural network is applied for predicting the heating and cooling loads using the experimental dataset. The used dataset is obtained by monitoring the impact of the building's dimensions on energy consumption. To optimize the training process of the multi-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The backpropagation is an optimization algorithm to further adjust the loss function and minimize the prediction error [60]. To improve its performance, regularization, dropout, batch normalization, activation functions and advanced optimization algorithms can be used [61].…”
Section: Methodsmentioning
confidence: 99%
“…The backpropagation is an optimization algorithm to further adjust the loss function and minimize the prediction error [60]. To improve its performance, regularization, dropout, batch normalization, activation functions and advanced optimization algorithms can be used [61].…”
Section: Methodsmentioning
confidence: 99%
“…The modelling model developed by Yan Zhang [175] using the Light Gradient Boosting Machine combined with the Shapley Additive exPlanation algorithm can predict the energy use and greenhouse gas emissions of residential buildings and identify the most influential variables. Yan's [108] multi-layer perceptron neural network can effectively predict the multi-energy load of buildings and found that the optimization algorithm impacts the prediction effect. Muhammad Faiq's team [182] used long short-term memory (LSTM) models and weather data to predict the energy consumption of institutional buildings, and the results were better than support vector regression (SVR) and Gaussian process regression (GPR).…”
Section: Algorithms and Deep Learning For Energy Efficiencymentioning
confidence: 99%
“…The energy consumed can be written in the following forms: Companies face the major challenge of estimating the time and cost to produce a given product (Yan et al, 2023). This task is particularly important in the case of CNC machining, where it is essential to determine the time and cost of each operation to select the most efficient machining sequence, taking into account both the cost and the energy required to perform it ( C Energy ).…”
Section: Materials and Measurementsmentioning
confidence: 99%